Punch drunk - Gringos Locos; Johnson, Richard G.; Asiala, Petri; Granfelt, Ben, 1963-; Manninen, Jyrki (Jyrki Johannes); Miettinen, Miri; Lönnholm, Kim; Strengell, Claes; Oakleaf, J. (Helsinki : Fazer Finnlevy, 1989)
13 kappaletta.
Gringos Locos (yhtye): Richard G. Johnson (laulu), Pete Asiala (bassokitara, laulu), Ben Granfelt (kitara, laulu), Muddy (kitara, laulu), Miri Miettinen (rummut, laulu). - Lisäksi: Kim Lönnholm (laulu), Claes Strengell (sähköurut), J. Oakleaf (laulu)
Äänitys: 1988.
Kuvailu Viola-tietokannasta 4.7.2017.
Keywords: Gringos Locos -- albumit; rock